FLOUTING MAXIMS AND THE IMPLICATIONS TO MAJOR CHARACTERS IN PAULO COELHOâS THE WINNER STANDS ALONE - Muslimin, Afif Ikhwanul (Journal on English as a Foreign Language (JEFL), 2014)
Communication needs the effectiveness of delivering information from the speaker to the hearer. Due to this reason, Griece offers to use the theory of cooperative principle to avoid misunderstanding between the speaker and hearer which consist of maxims. Aside from cooperative principle, Svoboda promotes politeness theory (maxims) that also has an enormous influence in a successful conversation. However, the speakers and the hearers as the participants of communication sometimes violate the maxims. The violation of maxims can cause flouting maxims. This paper is focused on analyzing flouting maxims on Igor as the main character in Paulo Coelhoâs The Winner Stands Alone novel context and their implications of those communication breakdowns to the other major characters in the novel. Referring to the descriptive analysis of the novel, it was revealed that Igor had violated maxims in the cooperative principle was denoted by various indicators, namely redundancy, less informative, out of topic, obscurity, ambiguity, and disorderliness. Moreover, sometimes Igor did not take account at othersâ feeling by violating six maxims in the politeness principle. Hence, Igor as the main character in the novel found himself in troubles in his relationship with girlfriends, wife, and colleagues. Finally, the findings can be used to raise the novel readersâ awareness on the importance of cooperative principle and politeness principle to be applied in real life communication in order to provide knowledge for the readers on how to apply language by making them aware of possible violation.Keywords: floating maxim, implications, major characters